PENERAPAN METODE ECONOMIC ORDER INTERVAL (EOI) DAN METODE PENGALI LAGRANGE DALAM PENGENDALIAN PERSEDIAAN BAHAN BAKU KERIPIK BAWANG - Rahmi, Nafia; Safitri, Elfira; Basriati, Sri; Sukmawati, Sri (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2025)
A common problem often faced by companie is the instability if the supply of raw materials needed by the company. Likewise, the Nadin’s Onion Chips Business has not implemented a stable raw materials inventory control system. The aim of this research is to control raw material inventory to determine the optimal inventory cost value. The methods used are Economic order Interval (EOI) and Lagrange Multplier. Based on the results, the cost of supplies for tapioca flour was IDR 429.204, wheat flour IDR 429.204, eggs IDR 151.514, garlic IDR 151.578, shallots IDR 172.706, celery IDR 107.301, vegetable oil IDR 239.918 , salt amounting to Rp. 177.822 and flavorings amounting to IDR. 176.394. Meanwhile, using the Lagrange Multiplier method produces inventory costs for tapioca flour of IDR 435.081, wheat flour of IDR 454.352, eggs of IDR 193.917, garlic of IDR 156.468, shallots of IDR 183.314, celery of IDR 113.702, oil vegetables amounting to IDR 243.355, salt amounting to IDR 183.053 and flavorings amounting to IDR 179.815. From the calculation results it can be concluded that the EOI method is more optimal than the Lagrange Multiplier method because EOI has minimum inventory costs.